Penser la musique aujourd'hui - Boulez, Pierre 1925-2016 (Mayance Editions Gonthier, 1963)
Livre doctrine de Pierre Boulez où il expose ce que devrait être la musique et comment l'aborder. Il faut 'donner à penser' et non pas expliquer les résultats.That the concept represented in popular aesthetics by avant-garde is applicable to music today, or in our century for that matter, would be hard to demonstrate. The idea that art has a continuous history that moves forward in both time and exploration is no less a trouble for dealing with the real artifacts, though a bit of it is required for explaining short-term developments like the classical symphony?Haydn through Schubert is only fifty years?or the growth of nontonal music from its germinal state of 1899 in Arnold Schoenberg?s Verklärte Nacht to the completed formulation of the twelve-tone method around 1923.The trouble with avant-garde, originally a term in military tactics, is that it assumes the adventures of individual and small-group experimenters to be justifiable only as they may open up a terrain through which some larger army will then be able to pass. But it fails to explain who constitutes this army and what is its objective, since a military advance, however massive, is not a migration. It cannot be the world public of concert subscribers and record buyers, since many important achievements, both unique and influential, arrive at such distribution far too meagerly and too late to serve culture consumption efficiently. The music of Erik Satie and of Schoenberg?s group are cases in point. It is all published now and largely recorded, but still not much played; the armies of musical exploitation, industrial and academic, have not carried it along with them in their world conquest.The idea that original work of this quality nourishes the younger composer is no less hard to justify. It becomes a part of his education, naturally; but his uses of it are inevitably dilutions, since innovations in art are generally brought to full term by their inventors (and a few close comrades) long before distribution gets hold of them. Actually, distributors tend to adopt only that which seems complete, presenting it as a novelty, which it may be for them, or as ?experimental,? which by this time it is not, save as a sales-line. Short-term developments certainly represent a true evolution. But incorporating them through the professional conservatories into the living tradition of music is a hit-or-miss affair, any occupation rights in these centers of power being reserved for successful modernists, themselves mostly diluters, if not polluters, of their sources. American universities have a way of taking up the more successful moderns, subjecting them to institutionally certified examination, and then sinking their remains in a mud puddle ironically called ?mainstream.?
Keywords: Music theory